PENGARUH GERAKAN LITERASI DAN MINAT BACA PESERTA DIDIK TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SMK KOTA TEGAL - Danang Hadi Wibowo dan Burhan Eko Purwanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2021)
This research is more focused and in-depth, the problems in this study are limited to the implementation of the school literacy movement towards the emergence of students' reading interest in Tegal City Vocational Schools. In this study there are two independent variables (independent) namely literacy movement and reading interest and one dependent variable (dependent) namely learning achievement. The hypotheses that will be followed up are, H0: there is no influence of literacy movement and reading interest on Indonesian language learning achievement and Ha: there is influence of literacy movement and reading interest on Indonesian language learning achievement.. Based on the results of the analysis conducted by the researcher, it was found that the sample in this study was 4 SMK in Tegal City including 2 State Vocational Schools and 2 Private Vocational Schools from class XI students. From the sample, the researcher will take as many as 200 students of class XI and 50 students from each school. There is a positive and significant influence between the school literacy movement and students' reading interest. The magnitude of the significance value is 0.006. In addition, there is a positive and significant influence between reading interest on student achievement. The magnitude of the significance value is 0.006. Finally, there is a positive and significant influence between the school literacy movement on student achievement. The magnitude of the significance value is 0.000.